Predictors of Knowledge, Attitudes, Practices and Barriers Regarding Sepsis and Sepsis Management Among Emergency Nurses and Physicians in Palestine: A Cross-Sectional Analysis - Basma Salameh PhD, RN; Ali Eyad Mahmoud Aboamash MSN, RN (SAGE Publishing, 2022)
Sepsis is a widespread problem that can create clinical and economic difficulties. This study aimed to determine the knowledge, attitudes, practices, and barriers related to the sepsis and sepsis management among emergency nurses and physicians. Data was collected using a self-questionnaire completed by the participating nurses and physicians (n = 243), with a 61% response rate. The study found that both emergency nurses and physicians had poor-to-moderate levels of sepsis knowledge, with emergency physicians having better attitudes regarding sepsis and sepsis management than emergency nurses. However, moderate knowledge levels of sepsis practice and management were shown among both nurses and physicians. It is evident that for emergency nurses and physicians, the biggest barrier to providing quality care to patients with sepsis is the lack of monitoring equipment. Both nurses and physicians need consistent sepsis management information provided by continual education programs. Development of an approved protocol can improve nurses' knowledge, attitudes, and practices.